Experimental Verification of the Adequacy of Mathematical Model of the Reciprocating Electric Electromagnetically Excited Generator - A. B. Menzhinski; A. N. Malashin; Yu. V. Sukhodolov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
The article presents a mathematical simulation of the electromagnetically excited generator of reciprocating type, which resulted in an equivalent circuit diagram, a magnetic circuit design of the generator and some expressions describing the electromagnetic processes in the electromagnetically excited generator of reciprocating type. The nonlinear mathematical model of the electromagnetically excited generator of reciprocating type has been developed. In order of the experimental verification of the adequacy of the mathematical model of the reciprocating electric generator, as well as of the validity of the assumptions made, a breadboard sample of the reciprocating electric generator has been made consisting of a fixed part in the form of two U-shaped magnetic cores and a moving part representing an H-shaped magnetic cores. There is focused operating winding on both the U-shaped magnetic cores. The N-shaped magnetic core is coiled with excitation winding which is connected to a DC power source. In a breadboard sample of the reciprocating electric generator a drive motor of 100 W with an amplitude of reciprocating oscillations of the moving part equal to 16 mm, and a frequency of oscillations adjustable in the range from 5 to 50 Hz is used in order to simulate a free-piston engine. The main characteristics of the generator (viz., idle speed and external characteristics) have been experimentally obtained. Comparison of experimental and calculated results demonstrated their discrepancy of no more than 4 %; therefore, the nonlinear mathematical model reflects the characteristics of the generator of longitudinal type with a high degree of adequacy.